Immunogenicity and safety of HepE Hecolin® in chronic hepatitis B patients at clinically stable stage: An open-label study in China - Li Zhang; Qiufen Zhang; Jiaye Liu; Wenlong Wu; Zechun Jiang; Bingyu Yan; Qingfan Cao; Haidong Liu; Huirong Pan; Jingjing Lv; Yi Feng; Fujie Xu; et al. (Human Vaccines & Immunotherapeutics)
Acute hepatitis E infection could induce severe outcomes among chronic hepatitis B (CHB) patients. Between 2016 and 2017, an open-label study was conducted to evaluate the immunogenicity and safety of hepatitis E vaccine (HepE) in CHB patients, using healthy adults as parallel controls in China. Eligible participants who were aged ≥30 y were enrolled in the study. The CHB group included participants who had ever developed symptoms of hepatitis because of CHB but was currently at a clinically stable stage, which was defined as ALT ≤ 1.5 times of upper limit of the normal range (ULN) in this study. The control group included healthy adults who had hepatitis B surface antigen (HBsAg) negative. HepE was administered for 0, 1, 6 months for all participants. At 1 month after the third-dose vaccination (month 7), the seroconversion rates of anti-HEV IgG were >97% in both groups. The geometric mean concentration (GMC) of anti-HEV IgG in the CHB group was non-inferior to the healthy adult group (0.69 WU/mL, 95% CI 0.55–0.85). The proportion of the participants with adverse events ≥ grade 3 was similar in both groups (p = .99), and no vaccine-associated severe adverse events were identified. Changes in the liver function indicators were not of clinical significance. The HepE was highly immunogenic and well tolerated among clinically stable CHB patients and healthy adults.